Preference Of Travellers For Sustainable Transportation Planning Objectives In Klang Valley, Malaysia. - Vien Leong, Lee; Sim Ho, Jen; Mohd Sadullah, Ahmad Farhan (2009)

(untitled)
Achieving sustainable transportation is a global aim today. However, the actual implementation of sustainable principles is severely challenging the decision-makers.Various efforts attempted to reduce the ownership of private vehicles have not been fruitful. The failures may be attributed to the fact that public transport services are unable to provide effective travel needs as offered by cars.